PENGGUNAAN EVALUASI MODEL CIPP PADA IMPLEMENTASI KEBIJAKAN PENILAIAN PRESTASI KERJA PEGAWAI NEGERI SIPIL KOTA TANGERANG SELATAN - Erialdy, Erialdy; Prastowo, Sugeng Lubar; Permana, Ade Indra (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2020)
On behalf to produce an excellent service, Civil Servants have to work professionally, certainly through coaching and supervision. Accordingly, the effective assessment method to measure working achievement objectively is required. In this effort, South Tangerang City has issued a policy of South Tangerang City’s Mayor Regulation No. 5 of 2018. Policy implementation evaluation used CIPP evaluation model, starts from policy purpose, implementation process to the result of the policy implementation. The research method used is a descriptive qualitative, the research instruments used are observation, interview and documentation study. The analysis of data research uses 4 steps ie. data collection, data reduction, data presentation and conclusion drawing or verification. Data validation testing used is source triangulation techniques. The appraisal of working achievement is used as a basic preparation for the arrangement of reasonable and transparent incentive system, a fair career development and evaluation for to the Local Government of South Tangerang city to its resources.